The crickets of genus Zvenella Gorochov, 1988 (Gryllidae: Podoscirtinae) from China - Ma, Libin; Zhang, Yalin (Zootaxa, 2012)
Three species of genus Zvenella from China are reviewed and the species Zvenella acutangulata Xia, Liu & Yin, 1991 is redescribed and illustrated. Three additional new species, Zvenella scalpratus sp. nov., Zvenella aequalis sp. nov. and Zvenella decussatus sp. nov., are described and reported from Hainan and Yunnan Provinces, China.